PENGARUH LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT UNIVENUS - Muhammad Fahril Ma’ruf; Menur Kusumaningtyas (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
The effectiveness of a business is significantly impacted by the productivity of its employees, and all businesses constantly work towards enhancing productivity in order to reach their objectives. The purpose of this study is to investigate how the work environment and leadership approach are affecting the performance of employees at PT Univenus. This research was conducted using a qualitative approach method. Data collection techniques using semi-structured interviews. The study involved analyzing data from interviews using qualitative methods. The findings indicate that both workplace environment and leadership approach play crucial roles in determining employee performance and productivity. A welcoming and encouraging work atmosphere, along with strong leadership, has the ability to inspire workers to increase their efforts, enhance their performance, and reach the goals of the organization.